Lactose malabsorption in systemic sclerosis. Issue 10 (28th September 2016) - Marie, I.; Leroi, A‐M.; Gourcerol, G.; Levesque, H.; Menard, J‐F.; Ducrotte, P.
Summary: Background: There are no studies on systemic sclerosis (SSc) assessing the relationship between food intake, especially lactose, and gastrointestinal dysfunction. Aim: To determine the prevalence of lactose malabsorption, using lactose breath test, in patients with SSc. To evaluate the correlation between lactose malabsorption and gastrointestinal involvement. To predict which SSc patients exhibit lactose malabsorption. Methods: Seventy‐seven consecutive Caucasian patients with SSc and 20 control subjects underwent lactose breath test. All patients also completed a questionnaire on digestive symptoms, and a global symptom score (GSS) was calculated. Results: The prevalence of lactose malabsorption was higher in SSc patients than in controls (44.3% vs. 10%; P  = 0.004). We observed a marked correlation between the presence of lactose malabsorption and: higher values of GSS ( P  < 0.0001); severe oesophageal ( P  = 0.018) and small intestinal ( P  = 0.04) motor disorders; and joint involvement ( P  = 0.019). Furthermore, in SSc patients with symptomatic lactose malabsorption, the median value of GSS of digestive symptoms was lower after initiation of lactose‐free diet ( P  < 0.0001). Conclusions: Our study underscores the fact that lactose malabsorption often occurs in patients with systemic sclerosis. Furthermore, our findings highlight the fact that lactose breath test is a helpful, noninvasive method, by identifying the group of patients with systemic sclerosis with symptomatic lactose malabsorption that may benefit from a reduction in lactose intake.